2014
DOI: 10.4236/ojst.2014.41007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoking on periodontal disease: An evidence-based comprehensive literature review

Abstract: The direct link between smoking, lung diseases, cancer, cardiovascular disease and poor pregnancy outcomes, such as miscarriage and low birth weight, has been extensively studied. In the past three decades, there has also been an increasing awareness of the impact of smoking on periodontal disease. Smoking is considered the major environmental risk factor in the prevalence, extent and severity of periodontal disease. This review article will attempt to build on previous studies in the periodontal literature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 75 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…Of all the oral habits that can be picked up because of stress, smoking is the one which has the most damaging effect on the periodontium [32,38] since: -the frequency of periodontal disease is 7-8 times greater for smokers than for nonsmokers [39]; -the severity of periodontal disease is higher among smokers (depth of periodontal pockets, periodontium, and bone attachment losses) [40];…”
Section: Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the oral habits that can be picked up because of stress, smoking is the one which has the most damaging effect on the periodontium [32,38] since: -the frequency of periodontal disease is 7-8 times greater for smokers than for nonsmokers [39]; -the severity of periodontal disease is higher among smokers (depth of periodontal pockets, periodontium, and bone attachment losses) [40];…”
Section: Smokingmentioning
confidence: 99%
“…-smokers respond less favorably to periodontal treatments whether they be nonsurgical, surgical, and/or medically [39,40].…”
Section: Smokingmentioning
confidence: 99%
“…Smoking exerts a major impact on the pace of progression of periodontal disease [28,29]. While a non-smoker who maintains good oral hygiene is rather likely to develop a rate of bone loss lower than 0.25 (% of bone loss divided by age), a patient who smokes more than 10 cigarettes a day can be suspected to lose over four times more bone [30,31].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…In addition, an average Polish smoker is estimated to smoke between 15 and 30 cigarettes daily, and the numbers are similar in other countries. The World Health Organization (WHO), in On the Global Tobacco Epidemic, 2021 -Addressing New and Emerging Products, reported that the prevalence of smoking among people over 15 years decreases from 22.7% to 17.5% [29,30,32]. Furthermore, worldwide, 1.1 billion people are considered smokers, and by 2025 this number is expected to increase to as much as 1.3 billion [33].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…Smoking has been implicated as an etiological agent for various chronic diseases, including infections, cancers, heart diseases, and chronic lung diseases, which together are the leading causes of morbidity and mortality in the world [2]. Cigarette smoking has been associated with periodontal disease for the past 20 years [3], but smoking alone does not cause periodontal disease. Periodontal disease is caused by bacterial plaque that accumulates underneath gingival tissues and becomes infected, initiating bone loss around the teeth.…”
Section: Introductionmentioning
confidence: 99%